Dynamics within the CD95 death-inducing signaling complex decide life and death of cells - Neumann, Leo; Pforr, Carina; Beaudouin, Joel; Pappa, Alexander; Fricker, Nicolai Benjamin; Krammer, Peter H.; Lavrik, Inna N.; Eils, Roland (Molecular systems biology, 2010)
This study explores the dilemma in cellular signaling that triggering of CD95 (Fas/APO-1) in some situations results in cell death and in others leads to the activation of NF-?B. We established an integrated kinetic mathematical model for CD95-mediated apoptotic and NF-?B signaling. Systematic model reduction resulted in a surprisingly simple model well approximating experimentally observed dynamics. The model postulates a new link between c-FLIPL cleavage in the death-inducing signaling complex (DISC) and the NF-?B pathway. We validated experimentally that CD95 stimulation resulted in an interaction of p43-FLIP with the IKK complex followed by its activation. Furthermore, we showed that the apoptotic and NF-?B pathways diverge already at the DISC. Model and experimental analysis of DISC formation showed that a subtle balance of c-FLIPL and procaspase-8 determines life/death decisions in a nonlinear manner. We present an integrated model describing the complex dynamics of CD95-mediated apoptosis and NF-?B signaling.
Gesehen am 12.05.2023